Common structural features of different viroids: serial arrangement of double helical sections and internal loops. - Langowski, J (1978)
The thermodynamic parameters of five different highly purified viroid "species" were determined by applying UV-absorption melting analysis and temperature jump methods. Their thermal denaturation proved to be a highly cooperative process with midpoint-temperatures (Tm) between 48.5 and 51 degrees C in 0.01 M sodium cacodylate, 1 mM EDTA, pH 6.8. The values of the apparent reaction enthalpies of the different viroid species range between 3,140 and 3,770 kJ/mol. Although the cooperativity is as high as found in homogeneous RNA double helices the Tm-value of viroid melting is more than 30 degrees C lower than in the homogeneous RNA. In order to explain this deviation, melting curves were simulated for different models of the secondary structure of viroids using literature values of the thermodynamic parameters of nucleic acids. Our calculations show that the following refinement of our earlier model is in complete accordance with the experimental data: In their native conformation viroids exist as an extended rodlike structure characterized by a series of double helical sections and internal loops. In the different viroid species 250-300 nucleotides out of total 350 nucleotides are needed to interprete the thermodynamic behaviour.